TINJAUAN HUKUM ISLAM TENTANG MENAFKAHI KELUARGA DENGAN HASIL JUDI ONLINE - Ahmad Mu’is; Selli Mariyana Hasibuan; Zaianal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
Nafkah is a property that is given to people who are obliged to earn a living, food, clothing and shelter are one part of a living. And those who are part of the breadwinners are wives, parents, slaves, small children, and pregnant women who have been divorced and are in a state of iddah. Even so, that's not the only thing that can earn a living, because our pets also have the right to earn a living. And as for the obligation to provide a living, the most basic is a living from parents, where parents have an obligation to provide a living for their children. However, in this case, a husband also has an obligation to provide for his wife, so that in this modern era many parents have used technology as an ingredient in earning a living, one of which is to make a living with the results of online gambling.